Power Learning Strategies for Success in College and Life. - Feldman Robert S. (McGraw-Hill, 2005)
The only first-year experience text with a unifying system for critical thinking and problem solving, P.O.W.E.R. Learning maximizes students’ potential for success in college and in life. Using the simple, class-tested principles of the P.O.W.E.R (Prepare, Organize, Work, Evaluate, and Rethink) system, students gain a sense of mastery and achievement as they move through the text; with the growth of their confidence comes the increased intellectual enthusiasm and personal discipline needed for them to excel. The 2005 edition of P.O.W.E.R Learning offers customizable modules regarding transfer students, student athletes, and career opportunities.